Experimental study of the deformation recovery characteristics of steel deck pavement materials. (27th September 2021) - Fan, Xiangyang; Luo, Rong
Highlights: Internal stress was measured by a repeated creep progressive loading recovery test. The feasibility of calculating the recovery modulus by creep test was confirmed. The recovery modulus was used to evaluate the cooperative deformation performance. Abstract: Steel deck pavement material and steel decks require good cooperative deformation ability. The deck system of a long-span steel bridge is flexible, and its pavement is repeatedly subjected to tensile stress and compressive stress; therefore, the steel deck pavement material requires a strong capability to recover from the deformation. The internal stress of the pavement material is the force driving its deformation and recovery. In this study, based on the characteristics of steel deck pavement materials, a repeated creep progressive loading recovery test (RCSR) was proposed to measure the internal stress. In addition, the theoretical solution of the internal stress of the material in the nondestructive stage was derived. The test results show that the RCSR test is effective and accurate in determining the internal stress of the steel deck pavement materials. The recovery modulus of a material can be defined by measurement and calculation of the internal stress. Moreover, different materials can be used to characterize the recovery modulus of a steel deck. Based on the theoretical solution of internal stress, the theoretical solution of the recovery modulus was deduced and calculated. The test value was used to determine the accuracy of the theoretical solution of the recovery modulus. The results were used to verify that the recovery modulus is the inherent property of the material in the nondestructive stage and is not affected by the additional conditions of the test. The internal stress and recovery modulus of three typical steel deck pavement materials were measured and calculated in this study. The test results show that an epoxy asphalt mixture has the largest recovery modulus, which indicates that under the same stress level, the internal driving force for the deformation recovery of this mixture is greater, and its deformation recovery ability is strongest.